Socio-legal perspectives on the adjudication of cultural diversity disputes in international economic law - Vadi, Valentina (Oñati Socio-Legal Series, 2011)
This article explores and critically assesses the recent case law adjudicated by WTO panels and investment arbitral tribunals on cultural diversity related disputes. Adopting a socio-legal approach, this study focuses on the role that adjudicators have played in mapping the interactions between international economic law and the international cultural law i.e. international law protecting cultural diversity. While arbitrators have started to accommodate cultural values in argumentation patterns, WTO panels and even the WTO Appellate Body have adopted a more cautious approach. This paper identifies the socio-legal reasons that may contribute to these different approaches. This study will proceed as follows. First, I will briefly define the multifaceted concept of cultural diversity and sketch out the relevant UNESCO instrument. Second, I shall analyze the available dispute settlement mechanisms. Third, the conflict areas between international economic law and cultural diversity law will be scrutinized through the analysis of some relevant case studies. Fourth, this contribution critically assesses the role that adjudicators play in adjudicating interdisciplinary disputes. Finally, some conclusions will be drawn.